THE ROLE OF RELATIONSHIP IN DIRECTING AND ACTING ARTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, Relationship is the basic law of behavior and vitality. The factor of spiritually guided behavior is relationship. Through relationship, a certain fact is accepted and influences another person, or a certain decision is made. Relationship determines the level of circumstances. It depends on the human psyche and affects the given circumstances. Relationship arises through internal monologue. Relationship can give rise to a new goal, and sometimes it can interfere with that goal. Relationship also determines what actions to take in given circumstances.